Peran Aktivitas Unplugged dalam Meningkatkan Keterampilan Berpikir Komputasional Siswa Sekolah Dasar - Rahman, Abdul; Dewantara, Brezto Asagi; Rini, Sulistyo (Universitas Muhammadiyah Magelang, 2026)
This study aims to present a current literature review on the role of unplugged activities in improving elementary school students' computational thinking skills. The study used a structured narrative review method for 10 key articles. Analysis was conducted by identifying and coding data from each article to generate key themes. The results of the analysis indicate that unplugged activities are effective in improving students' computational thinking skills based on the findings of quasi-experimental studies and meta-analyses. Unplugged activities also have a holistic impact, not only improving cognitive outcomes but also strengthening students' motivation and self-efficacy. Furthermore, the study highlights the unplugged-first model as an effective pedagogical practice, discusses the use of computational thinking assessment instruments such as TechCheck, and emphasizes the importance of teacher professional development and adaptation of unplugged activities in the context of artificial intelligence. This study provides practical implications for teachers, curriculum developers, and policymakers, particularly in the integration of unplugged activities and the balanced allocation of learning resources. Furthermore, this study proposes a future research agenda that includes longitudinal studies, instructional differentiation, cross-disciplinary transfer, ethical literacy in artificial intelligence, and the development of computational thinking learning models.